The Conflict of Forest Tenure and the Emergence of Community Based Forest Management in Indonesia - ANAND, PB; PURNOMO, EKO PRIYO (Universitas Muhammadiyah Yogyakarta, 2014)
The forest tenure policy remains a controversy in Indonesiaspecially, on the issues of how to maintainforest on sustainable way and at the same time howto share of benefit of forest resources to the localcommunities. Yet, the state is the main actor onforest tenure in Indonesia could not succeed to doso.. This paper discusses the Community BasedForest Management (CBFM) programme inIndonesia with some details relating to theIndonesian political and legal basis on land andnatural resources. This paper also describes theconflict of forest resources and the state’s failure inforest resources management in Indonesia. CBFMcan be used as an alternative to share resourcesand conserve the forest by engaging localcommunities.Key words: Conflict of resources, forest tenure,forest management and CBFM.